(untitled) (Research, Society and Development, 2021)
The wind source in the production of electric energy has been gaining more and more space in Brazil and in the world, because besides being clean energy, it has numerous benefits that are of global and economic interest. Thus, the objective of this study is to show recent data on the evolution of wind energy capacity in Brazil; the COVID-19 impacts on the wind industry in the national sector and demonstrate the issues related to the current scenario of the wind sector. Methodology, is a bibliographic study, of qualitative nature. Results obtained: in recent years, wind energy has grown significantly and even with the current global economic crisis, data show that the wind sector is expanding in the country and that the generation expects a promising future, as Brazil has great potential in wind resources that still need to be explored.